2014
DOI: 10.3391/bir.2014.3.1.07
|View full text |Cite
|
Sign up to set email alerts
|

New records of the invasive crabs Callinectes sapidus Rathbun, 1896 and Percnon gibbesi (H. Milne Edwards, 1853) along the Italian coasts

Abstract: Laonome calida Capa, 2007, a feather-duster worm discovered in 2007 in estuaries and open water of tropical and subtropical Australia, was recently found at many locations in fresh and brackish waters of the delta region of the rivers Rhine, Meuse, and Scheldt in the Netherlands. Morphological differences between specimens from Australia and the Netherlands are insufficient to warrant specific distinction. A recent translocation from Australia to Europe, or from a third country to both, may explain the disjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Among the numerous species considered to be invasive in coastal environments around the world, many decapod crustaceans have been recorded, such as Carcinus maenas (Linnaeus, 1758) (Geller et al ., 1997); Callinectes sapidus Rathbun, 1896 (Stasolla & Innocenti, 2014; Garcia et al ., 2018); Charybdis hellerii (A. Milne-Edwards, 1867) (Campos & Türkay, 1989; Mantelatto & Luiz-Diaz, 1999; Dineen et al ., 2001; Evans et al ., 2018); Lysmata lipkei Okuno & Fiedler, 2010 (Alves et al ., 2018); Lysmata vittata (Stimpson, 1860) (Abdelsalam, 2018; Alves et al ., 2018, 2019); and Nikoides sibogae De Man, 1918 (Levitt et al ., 2014). However, the invasive potential of a species depends on morphological, reproductive, metabolic and life-history aspects, which are related to the phenotypic plasticity of the species (Lardies & Bozinovic, 2008; Lenz et al ., 2018; Negri et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous species considered to be invasive in coastal environments around the world, many decapod crustaceans have been recorded, such as Carcinus maenas (Linnaeus, 1758) (Geller et al ., 1997); Callinectes sapidus Rathbun, 1896 (Stasolla & Innocenti, 2014; Garcia et al ., 2018); Charybdis hellerii (A. Milne-Edwards, 1867) (Campos & Türkay, 1989; Mantelatto & Luiz-Diaz, 1999; Dineen et al ., 2001; Evans et al ., 2018); Lysmata lipkei Okuno & Fiedler, 2010 (Alves et al ., 2018); Lysmata vittata (Stimpson, 1860) (Abdelsalam, 2018; Alves et al ., 2018, 2019); and Nikoides sibogae De Man, 1918 (Levitt et al ., 2014). However, the invasive potential of a species depends on morphological, reproductive, metabolic and life-history aspects, which are related to the phenotypic plasticity of the species (Lardies & Bozinovic, 2008; Lenz et al ., 2018; Negri et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a juvenile specimen of C. feriata was found in the sediment of ballast water tanks of a ship docking in Germany (Gollasch, 2002). Although C. feriata actually seem to be rare in the Mediterranean Sea, we cannot exclude the possibility of a future spread in the Basin, as in the case of the invasive Atlantic species Callinectes sapidus (Stasolla & Innocenti, 2014).…”
Section: First Occurrence Of the Tropical Indo-west Pacific Head-shiementioning
confidence: 92%
“…The first confirmed record for the Mediterranean is dated back to 1948 (GIORDANI SOIKA, 1951), although its presence was suspected as early as 1935 (NEHRING, 2011). In Italian waters, the majority of records were from the Adriatic and Ionian seas (STASOLLA & INNOCENTI, 2014;MANFRIN et al, 2016;AZZURRO et al, 2019), while in western Italy the species was reported only from Sardinia (PIRAS et al, 2019), Liguria (MAN-CINELLI et al, 2017;SUARIA et al, 2017) and Tuscany (FROGLIA, 2017). With the exception of Sardinia, the area of the Strait of Messina and the northern Tyrrhenian Sea (CAVALIERE & BERDAR, 1975;BISCONTI & SILVI, 2005;GIACOBBE et al, 2019;CULURGIONI et al, 2020), no records were reported from the Tyrrhenian Sea in the wide coastal tract extending from Latium to Calabria.…”
Section: Introductionmentioning
confidence: 99%